Synthesis and biological evaluation of 6H-1-benzopyrano[4,3-b]quinolin-6-one derivatives as inhibitors of colon cancer cell growth (Bangladesh Journal of Pharmacology, 2015)
A convenient synthesis of 6H-1-benzopyrano[4,3-b]quinolin-6-one derivatives was reported using 4-chloro-2-oxo-2H-chromene-3-carbaldehyde with different aromatic amines using silica sulfuric acid. The compounds were tested for their anticancer activity against colon (HCT-116 and S1-MI-80), prostate (PC3 and DU-145), breast (MCF-7 and MDAMB-231) cancer cells. These com-pounds showed more selectivity and potent cytotoxic activity against colon cancer cells. 3c was tested against five other colon cancer cell lines (HT-29, HCT-15, LS-180, LS-174, and LoVo), which had similar cytotoxicity and selectivity. 3c did not induce PXR-regulated ABCB1 or ABCG2 transporters. In fact, 3c induced cytotoxicity in HEK293 cells over expressing ABCB1 or ABCG2 to the same extent as in normal HEK293 cells. It was cytotoxic approximately 3- and 5-fold to resistant colon carcinoma S1-MI-80 cells. 3c also produced concentration-dependent changes in HCT-116 colon cancer cells, in mitochondrial membrane potential, leading to apoptosis, and sub-micromolar concentrations caused chromosomal DNA fragmentation.